Analysis of E-Learning Media in Islamic Religious Education from A Neuroscience Perspective - Husain, Andi Musthafa; Suyadi; Prawironegoro, Djamaluddin; Bustam, Betty Mauli Rosa; Wantini (Universitas Islam Indonesia, 2024)
This study explores the integration of e-learning media in Islamic Religious Education (PAI) at SDN Somoitan from a neuroscience perspective. A qualitative case study approach was employed, involving in-depth interviews, classroom observations and supporting documents. Data analysis was conducted using a descriptive approach to illustrate the impact of e-learning on students' cognitive functions, particularly in the context of neuroplasticity, attention, and memory retention. The findings reveal that e-learning media incorporating visual and auditory elements positively impacts student participation. The use of videos, animations, and interactive quizzes helps students better understand the material, aligning with neuroplasticity principles that demonstrate the brain's ability to adapt through diverse learning experiences. However, the study also identifies challenges in implementing e-learning, including technological infrastructure limitations, such as unstable internet connections, and teachers' competency in integrating technology into the learning process. Despite these challenges, the school has made efforts to improve infrastructure and provide training to teachers to enhance their technical skills. This study offers valuable insights into how e-learning media can be optimized to improve student learning outcomes and provides strategic recommendations to address existing barriers. The study concludes that, despite the challenges, the effective implementation of e-learning media can have a significantly positive impact on the quality of education at SDN Somoitan.